Применение итерационных методов для численного анализа стационарных конфигураций плазмы - Шерстнюк, Д. В. (ХНУРЕ, 2013)
Рассмотрены некоторые вопросы решения, единственности и устойчивости в двумерных задачах плазмостатики с цилиндрической геометрией и винтовым магнитным полем, которые сводятся к краевым задачам нелинейного эллиптического уравнения Грэда-Шафранова. Приведены примеры неединственных и неустойчивых решений. Схема исследования и полученные результаты являются типичными для большого класса двумерных моделей конфигураций плазмы. During the numerical investigation of a plasma cylinder in magnetic field of some helical conducting wires in equilibrium, we discuss some questions on the solution, uniqueness and stability in boundary problems with the nonlinear elliptic Grad-Shafranov equation. Some examples of nonunique and unstable solutions are given. A spectral analysis of the linearized equation made possible to determine a restriction of admissible parameter values and to specify iterative methods of solving the problem. The scheme investigation and a general nature of obtained results are typical for a large class of two-dimensional models of static magnetoplasma configurations.
Keywords: двумерная задача плазмостатики; цилиндрическая геометрия; винтовое магнитное поле; уравнения магнитной гидродинамики; дифференциальное уравнение типа Грэда-Шафранова; nonlinear elliptic Grad-Shafranov equation; two-dimensional problem of plasmastatic; helical magnetic field